THE EFFECT OF TRUST AND PRICE ON PURCHASE DECISIONS THROUGH BRAND IMAGE AS INTERVENING VARIABLES (CASE STUDY OF SHOPEE USERS IN MAKASSAR CITY) - Abdul Rahman Azis; Muhammad Asdar; Abdul Razak Munir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This study aims to explain the effect of trust and price on purchasing decisions through brand image as an intervening variable (a chase study of Shopee users in Makassar). The research sample of 100 Shopee users. The analytical method used is path analysis with the help of SPSS ver 25 application. The results showed that the trust and price variables had a positive effect on purchasing decisions through brand image.